ANALYSIS OF THE IMPACT OF COVID-19 ON POVERTY IN BANDUNG-INDONESIA: SOCIOLOGY-RELIGION-ISLAMIC PERSPECTIVE CONCEPT APPROACH - Mafruhat, Ade Yunita; Alfadhillah, Farah Hanieva; Fadhillah, Nida Awwali Zahratul; Wildani, Widya Nissa; Haviz, Meidy; Noviani, Noviani (Universitas Islam Negeri Ar-Raniry, 2025)
This article aims to analyze in depth the impact of Covid-19 on conditions of spiritual poverty, especially indicators of aqidah associated with material poverty conditions, especially socio-cultural indicators in urban areas of Indonesia, namely Bandung City based on the theory of the sociology of religion. Bandung City is the capital city of West Java Province where West Java itself is one of the provinces with the largest contributor to poverty in Indonesia. Based on the existing literature, poverty is an obstacle to development. The question is, what are the conditions of poverty, both spiritual poverty (aqidah) and material poverty conditions (social-cultural) in the city of Bandung? Does Covid-19 have an impact on these two conditions of poverty? If yes, What are the impacts due to Covid-19? To answer this question, the methodology used is a mix method using a different test and the study sample taken is 100 poor households in the city of Bandung spread over 30 sub-districts. The results of the study show that there is an impact of Covid-19 on aspects of aqidah poverty and social material poverty aspects.